In Situ Synthesis of Core-Shell-Structured SiCp Reinforcements in Aluminium Matrix Composites by Powder Metallurgy - Xinghua Ji; Cheng Zhang; Shufeng Li (Metals, 2021)
SiCp reinforced aluminium matrix composites (AMCs), which are widely used in the aerospace, automotive, and electronic packaging fields along with others, are usually prepared by ex situ techniques. However, interfacial contamination and poor wettability of the ex situ techniques make further improvement in their comprehensive performance difficult. In this paper, SiCp reinforced AMCs with theoretical volume fractions of 15%, 20%, and 30% are prepared by powder metallurgy and in situ reaction via an Al-Si-C system. Moreover, a combined method of external addition and an in situ method is used to investigate the synergistic effect of ex situ and in situ SiCp on AMCs. SiC particles can be formed by an indirect reaction: 4Al + 3C → Al4C3 and Al4C3 + 3Si → 3SiC + 4Al. This reaction is mainly through the diffusion of Si, in which Si diffuses around Al4C3 and then reacts with Al4C3 to form SiCp. The in situ SiC particles have a smooth boundary, and the particle size is approximately 1–3 μm. A core-shell structure having good bonding with an aluminium matrix was generated, which consists of an ex situ SiC core and an in situ SiC shell with a thickness of 1–5 μm. The yield strength and ultimate tensile strength of in situ SiCp reinforced AMCs can be significantly increased with a constant ductility by adding 5% ex situ SiCp for Al-28Si-7C. The graphite particle size has a significant effect on the properties of the alloy. A criterion to determine whether Al4C3 is a complete reaction is achieved, and the forming mechanism of the core-shell structure is analysed.